2017
DOI: 10.1007/s00374-017-1247-4
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient limitations to bacterial and fungal growth during cellulose decomposition in tropical forest soils

Abstract: Nutrients constrain the soil carbon cycle in tropical forests, but we lack knowledge on how these constraints vary within the soil microbial community. Here, we used in situ fertilization in a montane tropical forest and in two lowland tropical forests on contrasting soil types to test the principal hypothesis that there are different nutrient constraints to different groups of microorganisms during the decomposition of cellulose. We also tested the hypotheses that decomposers shift from nitrogen to phosphorus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(46 citation statements)
references
References 56 publications
(71 reference statements)
1
35
1
9
Order By: Relevance
“…Our data on the ratio of bacterial/fungal growth (Figure a) showed relatively more bacterial than fungal growth at lower MAT in the highland soils. Our results might thus suggest that earlier studies indicating fungal dominance in cold environments may be explained by other environmental factors covarying with temperature (e.g., N availability; Nottingham, Hicks, et al (); Nottingham, Turner, et al ()). A further complicating factor is that the methodology provides proxies for bacterial and fungal growth and there may be small methodological errors when comparing results for bacterial growth (method reflects protein synthesis) with results for fungal growth (method reflects membrane synthesis).…”
Section: Discussionmentioning
confidence: 99%
“…Our data on the ratio of bacterial/fungal growth (Figure a) showed relatively more bacterial than fungal growth at lower MAT in the highland soils. Our results might thus suggest that earlier studies indicating fungal dominance in cold environments may be explained by other environmental factors covarying with temperature (e.g., N availability; Nottingham, Hicks, et al (); Nottingham, Turner, et al ()). A further complicating factor is that the methodology provides proxies for bacterial and fungal growth and there may be small methodological errors when comparing results for bacterial growth (method reflects protein synthesis) with results for fungal growth (method reflects membrane synthesis).…”
Section: Discussionmentioning
confidence: 99%
“…The highest content of selenium was reported for Sicilian hazelnut (86.5 µg/100 g) and Turkish Tombul hazelnuts (60 µg/100 g) [28,29]. The C, N, and P contents of HS are in the range of fungal biomass which varied from 38 to 57%, 0.23 to 15%, and 0.040 to 5.5%, respectively [30], indicating that HS might be a good nutrient for fungal growth. Fungi are known to have relatively higher C/P and C/N ratios, compared to bacteria, which may be related to their large size and small surface area to volume ratio, which decreases the relative demand for P-rich membrane phospholipids [31,32].…”
Section: Elemental Analysis and Metals Contents Of Hsmentioning
confidence: 95%
“…For the gut bacterial communities, there are distinct differences between the effects of added NP and added Na. For NP, it has been observed that soil bacterial and fungal communities similarly respond directly to added NP with increased growth and shifts in community composition (Lv et al, 2017;Nottingham et al, 2018). More specifically, added NP was shown to contribute both directly and indirectly to a decrease in microbial richness and shifts in microbial communities in fertilized soils (Campbell et al, 2010;Zeng et al, 2016).…”
Section: Bacterial Communitiesmentioning
confidence: 99%